Design of the Prototype Instrument for Measuring Freshness of Fish Based on Resistance - Subrata, I Dewa Made; Ibrahim, Bustani; Erungan, Anna C.; Tunas, Steven G. (Jurnal Keteknikan Pertanian, 2011)
The freshness of the dead fish is very difficult to be known visually whereas the use of chemical analyses is not only time consuming but also is not readily available at for market. Therefore, it is considered necessary to find out a newmethod for that purpose. In this. research, a prototype instrument for measuring freshness of the dead fish was designed based on the fish electrical resistance. The sensor was made of a couple of steel wires with diameter of 0.5 mm. During measurement, the wires sensor was inserted into the fish body with the distance of 2 cm to each other. Result of the research showed linear relationship between dead fish freshness and its resistance. The linear relationship was also found between water content of the fish body and its resistance.